Platformized Precarity, Religious Giving, and Welfare Authority in Indonesian Gig Work - Muhammad Syayid Ripai (Pen Of Political Authority and Religion, 2026)
Digital labor platforms have become influential sites of public power in Indonesia by governing access to livelihood, disciplining workers through algorithmic systems, and structuring the conditions under which economic survival remains possible. In urban gig work, this emerging platform authority operates alongside fragmented state welfare and non-state religious support, creating a layered regime in which legitimacy, obligation, and protection are distributed across unequal institutional actors. This article examines how platformized precarity in Indonesian gig work is governed through the interaction of algorithmic control, incomplete public welfare, and religiously mediated forms of support and legitimacy. It adopts a qualitative, theory-driven approach that integrates scholarship on platform labor, welfare governance, political authority, and moral economy. The discussion draws on academic literature, policy documents, platform-related public materials, and documented accounts concerning ride-hailing, delivery work, social protection gaps, and religious giving in Indonesia. Analytical attention is directed to four interconnected dimensions: platform authority, welfare fragmentation, religious support, and the displacement of responsibility across firms, state institutions, households, and moral communities. A mechanism-based synthesis is used to clarify how digital firms exercise practical governing power while non-state religious actors and obligations help absorb the social consequences of weak formal protection. Platformized precarity emerges as a condition in which platforms govern livelihood without assuming full welfare responsibility, while religious charity and moral obligation function as supplementary infrastructures of legitimacy and survival. Indonesian gig work therefore reveals a hybrid field of governance in which state authority remains partial, platform power expands, and religiously grounded support becomes central to the everyday management of insecurity. The article contributes to the field by offering a POLAR-relevant framework for understanding how religion shapes welfare legitimacy and public power under digital capitalism, and how weak political institutions redirect social protection into morally authorized non-state channels.